2013
DOI: 10.1158/1541-7786.mcr-12-0652
|View full text |Cite
|
Sign up to set email alerts
|

Activation of the FGF2-FGFR1 Autocrine Pathway: A Novel Mechanism of Acquired Resistance to Gefitinib in NSCLC

Abstract: Patients with non-small cell lung cancer (NSCLC) that harbors epidermal growth factor receptor (EGFR) mutations initially respond to EGFR-tyrosine kinase inhibitors (TKI) but eventually experience relapse. Acquired resistance to EGFR-TKIs is strongly associated with patient mortality. Thus, elucidation of the mechanism of acquired resistance to EGFR-TKIs is of great importance. In this study, gefitinib-resistant cell line models were established by long-term exposure to gefitinib using the gefitinib-sensitive … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

14
152
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 175 publications
(167 citation statements)
references
References 30 publications
14
152
1
Order By: Relevance
“…Similarly, we noted that fibroblast growth factor receptor (FGFR) family kinase genes FGFR1 and FGFR2, though not previously recognized as sufficient for EGFR bypass, nonetheless align with previous work describing up-regulation of FGFR1 as well as the ligand FGF2 in gefitinib-resistant NSCLC models, with concomitant dependency on the FGFR pathway (33,34), and with other studies implicating FGF ligands in TKI resistance (15,35).…”
Section: Discussionsupporting
confidence: 88%
“…Similarly, we noted that fibroblast growth factor receptor (FGFR) family kinase genes FGFR1 and FGFR2, though not previously recognized as sufficient for EGFR bypass, nonetheless align with previous work describing up-regulation of FGFR1 as well as the ligand FGF2 in gefitinib-resistant NSCLC models, with concomitant dependency on the FGFR pathway (33,34), and with other studies implicating FGF ligands in TKI resistance (15,35).…”
Section: Discussionsupporting
confidence: 88%
“…Co-inhibition with lapatinib sensitized these cells to FGFR inhibitor. Previous studies have also shown cross talk between FGFR and ERBB pathway in multiple tumor types [36][37][38] . In lung cancer, activation of FGFR pathway is a cause of acquired resistance to EGFR 21 inhibitors in EGFR mutant cancer cell lines 36 .…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies have also shown cross talk between FGFR and ERBB pathway in multiple tumor types [36][37][38] . In lung cancer, activation of FGFR pathway is a cause of acquired resistance to EGFR 21 inhibitors in EGFR mutant cancer cell lines 36 . Also, a switch from dependency on In conclusion, we have demonstrated that high FGFR1 protein expression is surprisingly absent in a significant number of FGFR1-amplified lung cancers, and these cancers are uniformly resistant to FGFR inhibitors.…”
Section: Resultsmentioning
confidence: 99%
“…Both EGFR and FGFR have been reported to be overexpressed and likely contributors in ovarian cancer (36,64,65), and FGF3/EGFR cooverexpression also was reported in NSCLC (77). In addition, the activation of FGFR autocrine pathways were found to be individually responsible for acquired resistance to gefitinib (an EGFR inhibitor) in NSCLC, and combination treatments such as PD173074 and gefitinib were required to restore effective growth inhibition (78,79). Likewise, EGFR/ErbBs recently were reported to limit the sensitivity to FGFR inhibition in FGFR3-mutated or -translocated cell lines such as RT112 (FGFR3/TACC3 fusion) and MGHU3 (Y375C) (80,81), and the PD173074 and gefitinib combination displayed an obvious synergistic effect (80).…”
Section: Discussionmentioning
confidence: 99%